PENGARUH PROGRAM KELOMPOK BERMAIN GAMELAN JAWA TERHADAP KESEJAHTERAAN EMOSI DAN KETERAMPILAN SOSIAL PADA REMAJA - , Sarah Rachmawati, Prof. Dr. Sofia Retnowati, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study was aimed to test the effectiveness of Javanese Gamelan Group Program to increase level of emotional well-being and social skill in adolescents. The hypothesis proposed for this study was âJavanese Gamelan Group Program is effective to increase level of emotional well-being and social skill in adolescentsâ.The experimental group that received Javanese Gamelan Group Program experienced a increase level of emotional well-being and social skill compared to that of control group that did not received Javanese Gamelan Group Program. The subjects of this study were 16 students of SMP Negeri 2 and SMP Negeri 7 Magelang who were registered as active students, suffered average to low level of emotional well-being and social skill, and voluntarily participated in the program. They were assigned into two groups, group that received training (experimental group), consisting of 8 students, and group that did not receive program (control group), consisting of 8 students. PANAS-X was used during the selection of subjects as a screening to find out whether or not they had emotional well-being. School Social Behavior Scales (SSBC) was used during the selection of subjects as a screening to find out whether or not they had social skill. The experimental design for this study was a pretest-posttest control group design. The treatment was Javanese Gamelan Group Program on the experimental group. The multivariate mix design, that analyzed difference score between the experimental group and the control group, indicated that the Javanese Gamelan Group Program was effective in increase level of emotional well-being and social skill in adolescents. It was shown by the result of F = 13,844 dengan p = 0,001 (p<0,05). Thus, the Javanese Gamelan Group Program had an effective of 7,8% to increase emotional well-being and 12,2% to increase social skill among adolescent.